Effects of different induction methods and post-activation potentiation on lower limb muscle activation and explosive power - Zhang, Xingchen; Gao, Yuan; Sun, Yang; Li, Enjing (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the acute effects of a different-intensity resistance warm-up on lower limb isokinetic strength, muscle activation, and exercise performance under blood flow restriction.MethodsUsing an isokinetic dynamometer, surface electromyography (sEMG) system, and force platform, lower limb isokinetic strength characteristics, electromyographic parameters, jump kinetics, kinematics, and other relevant parameters were assessed in 15 healthy males following different warm-up induction protocols.ResultsIsokinetic strength testing:HBFR produced higher knee extension torque than LLRT at 3,6,12 min (P = 0.012, P = 0.028, P = 0.019) and surpassed LBFR at 9 min (P = 0.015). LBFR increased torque immediately post-warm-up (0 min vs pre: P = 0.049), while HBFR peaked at 3 min (P = 0.040). Jump performance: HBFR achieved greater flight height than LBFR (P = 0.002). At 6 min, LLRT showed lower peak power vs LBFR/HBFR (P = 0.046, P = 0.034). LBFR increased flight height at 3/6 min (P = 0.049, P = 0.045), HBFR at 0/3 min (P = 0.048, P = 0.020). EMG data: LBFR exhibited higher vastus lateralis RMS than HLRT at 9 min (P = 0.035). MPF differed significantly between groups across timepoints (P = 0.031, P = 0.026, P = 0.000, P = 0.047). HBFR increased vastus medialis RMS at 6 min (P = 0.032), while HLRT decreased MPF at 6/12 min (P = 0.019, P = 0.045).ConclusionHBFR warm-up amplifies regional ischemia by superimposing intrinsic and extrinsic constraints, synergistically enhancing neuromuscular recruitment and metabolic stress. This mechanism sustains elevated force output and potentiates PAP, albeit with elevated load-associated injury risks. LBFR warm-up achieves muscle activation comparable to high-intensity training under reduced mechanical loading. The temporal manifestation of PAP exhibits task-specific variability across performance metrics, necessitating individualized BFR protocol optimization and precise recovery time modulation based on target outcomes. Collectively, LBFR represents an efficacious warm-up strategy with minimized injury risk, as evidenced by the present findings.